DESCRIPTION OF THE INTRODUCTION TO THE SCHOOL FIELD (PLP) I ON THE IMPLEMENTATION OF THE STRENGTHENING ISLAMIC VALUES IN THE SCHOOL CULTURE TO SHAPE THE CHARACTER OF STUDENTS IN THE MUHAMMADIYAH 1 MIDDLE SCHOOL (SMP) SIDOARJO - Efendi, Nur; Mutiara Sukama; Fadhilah Nur Rachma; Nabilah Ardelia Arianto (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The PLP 1 aims to provide students with direct experience in understanding the school environment, including school culture, school management, and educator competencies. Method: This research uses qualitative descriptive research methods with observation and interview techniques to collect data. Results: The research results show that 1) PLP 1 activities provide great benefits for students in developing their professional competence and personality as prospective teachers, 2) the averages of the student’s interest: 3.62 and motivation: 3.81 which shows attitudes towards strengthening Islamic values and a good and positive school environmental culture to shape the character of the students in the SMP Muhammadiyah 1 Middle School (SMP) Sidoarjo, and 3) The implementation of the school environmental conditions, the school vision and mission, the school rules and regulations, and the ceremonial activities were carried out well, so that they can embrace the era of globalization. Novelty: The Introduction to the School Field (PLP) 1 is the initial stage in the learning process for prospective teachers.